Functional silsesquioxane-based hierarchical assemblies for antibacterial/antifungal coatings. Issue 5 (12th January 2015) - Bordianu, Irina-Elena; David, Geta; Simionescu, Bogdana; Aflori, Magdalena; Ursu, Cristian; Coroaba, Adina; Hitruc, Gabriela; Cotofana, Corneliu; Olaru, Mihaela
Abstract : This paper reports the first study on functional silsesquioxane-based hierarchical assemblies containing an ordered distribution of silver nanoparticles with a large number of {111} facets, obtained through sol–gel reaction, intended for antibacterial/antifungal coatings. Abstract : This paper reports the first study on functional silsesquioxane-based hierarchical assemblies containing an ordered distribution of silver nanoparticles with a large number of {111} facets, obtained through sol–gel reaction, intended for antibacterial/antifungal coatings.